The Qur’anic Methods in Instilling Characters in a family: An Educational Perspective - Herniawati, Ani; Hidayat, Yusuf; Hasanah, Aan; Arifin, Bambang Samsul (International Journal Corner of Educational Research, 2024)
Characters are closely related to morality which is underpinned on the moral strength based on the value system instilled as early as possible in a family. The study aims to discuss the Qur’anic methods used to instill the early childhood’s characters in a family. To gain the data, the researchers employ qualitative method under descriptive approach. In addition, to analyse the data, it is used content analysis technique. The results of the study assert that characters education needs to be taught and instilled as early as possible to early childhood at home. Through the education, the parents need an enormous efforts to instill characters education to the early childhood. One of the efforts is using the Qur’anic methods used to instill the early childhood’s characters in a family. The Qur’anic methods consist of the Amtsal method, the Kisah (story) method, the Ibrah Mauidzah method, the Targhib wa Tarhib method, the Tajribi method, the Uswah Hasanah method, and the Hiwar method. In conclusion, instilling characters to early childhood in a family needs the suitable methods, so that its implementation is going to be in harmony with planning and achieve the goal to create early childhood to be ‘Insan Kamil’.